2021
DOI: 10.1002/jssc.202100551
|View full text |Cite
|
Sign up to set email alerts
|

Dispersive liquid‐liquid microextraction method combined with sugaring‐out homogeneous liquid‐liquid extraction for the determination of some pesticides in molasses samples

Abstract: In this study, a sensitive analytical method was developed to determine some pesticides (cyprodinil, trifloxystrobin, prometryn, propachlor, fenitrothion, chlorpyrifos, profenofos, and phosalone) in molasses samples. Pesticides were extracted from samples by dispersive liquid‐liquid microextraction method combined with sugaring‐out homogeneous liquid‐liquid extraction and determined by gas chromatography–mass spectrometry analysis. In this method, pesticides in molasses samples were first extracted using a wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…Under the same conditions, aliquots of 1 g cherry jam sample were added with 1 ml of solvent/water mixture (50/50%, v/v) and subjected to vigorous shaking (1 min at 2500 rpm) and centrifuged at 6000 rpm for 4 min. The visual observations (Figure S1) showed that only ACN formed a two-phase system, while other solvents could not be separated from the aqueous solution, a result which is consistent with findings from several studies [16,19,20]. Therefore, ACN was selected as a water-miscible solvent for further studies.…”
Section: Type Of Water-miscible Solventsupporting
confidence: 88%
See 3 more Smart Citations
“…Under the same conditions, aliquots of 1 g cherry jam sample were added with 1 ml of solvent/water mixture (50/50%, v/v) and subjected to vigorous shaking (1 min at 2500 rpm) and centrifuged at 6000 rpm for 4 min. The visual observations (Figure S1) showed that only ACN formed a two-phase system, while other solvents could not be separated from the aqueous solution, a result which is consistent with findings from several studies [16,19,20]. Therefore, ACN was selected as a water-miscible solvent for further studies.…”
Section: Type Of Water-miscible Solventsupporting
confidence: 88%
“…The SULLME-HPLC/UV method is compared with recent methods reported in the literature [20,[27][28][29][30][31][32] for the determination of OPPs in some food samples, taking into account some performance parameters such as time required for basic operations, LOD, RSD, and recovery. Comparison details are summarized in Table 3.…”
Section: Analytical Performance Of the Proposed Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Up to now, much attention has been paid to this field and different sample preparation methods have been introduced. Among these methods, dispersive liquid-liquid microextraction (DLLME), that has been introduced in 2006 to overcome the problems associated with conventional liquid-liquid extraction (being tedious and consuming high volumes of toxic organic solvents), has gained an outstanding position [11,12]. In this approach, the extraction solvent is dispersed throughout the sample solution by means of a dispersive solvent, and the analytes are extracted into the produced fine droplets of extractant [13].…”
Section: Introductionmentioning
confidence: 99%